Successful aqueous processing of a lead free 0.5Ba(Zr0.2Ti0.8)O-3-0.5(Ba0.7Ca0.3)TiO3 piezoelectric material composition - Kaushal, Ajay (2017)
We report on the successful aqueous processing of a lead free piezoelectric 0.5Ba(Zr0.2Ti0.8)O-3-0.5( Ba0.7Ca0.3)TiO3 (BZT-BCT) composition with the final functional properties of the materials unaffected by the various processing steps involved. X-ray diffraction results show a single tetragonal perovskite crystalline phase for the as-received sintered BZT-BCT powder. The purity of the perovskite phase for BZT-BCT powder was found to be controlled even after ageing the material in water for 24 h as a successful surface treatment against hydrolysis. An aqueous suspension of surface treated BZT-BCT powder with 50 vol% solid loading was successfully transformed into micro-sized granules via a freeze granulation (FG) method. Various structural, electrical and mechanical properties of sintered BZT-BCT-FG and BZT-BCT-NG ceramics consolidated from freeze granulated and non-granulated (NG) powders, respectively, were measured. The dielectric constant (epsilon(r)) values of the BZT-BCT-FG sample were found to be higher, with lower dielectric loss (tan delta) values in comparison with those of a sample prepared from the BZT-BCT-NG powder at all temperatures and with all frequency ranges tested. Nanoindentation results revealed that the ability to oppose deformation was nearly 10-fold higher for BZT-BCT-FG (6.93 GPa) than for BZT-BCT-NG ceramics (543 MPa). The functional properties of BZT-BCT- FG samples confirmed the benefits of the aqueous processing approach in comparison with traditional dry pressing.